A companion to the antebellum presidents, 1837-1861 - Silbey, Joel H. (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2014)
A Companion to the Antebellum Presidents presents a series of original essays exploring our historical understanding of the role and legacy of the eight U.S. presidents who served in the significant period between 1837 and the start of the Civil War in 1861. Explores and evaluates the evolving scholarly reception of Presidents Van Buren, Harrison, Tyler, Polk, Taylor, Fillmore, Pierce, and Buchanan, including their roles, behaviors, triumphs, and failuresRepresents the first single-volume reference to gather together the historiographic literature on the Antebellu.
Introduction / Joel H. Silbey -- General themes. -- The political world of the antebellum presidents / Joel H. Silbey -- The expansionist impulse in antebellum America / Michael A. Morrison -- The rise of sectional tensions; parties, slavery and abolitionism / Nicole Etcheson -- The antebellum presidents and foreign policy / Jay Sexton -- The presidents. -- Martin Van Buren as party leader and at Jackson's right hand / M. Philip Lucas -- Van Buren and the economic collapse of the 1830s / Jonathan M. Atkins -- "Tippecanoe and Tyler too": William Henry Harrison and the rise of popular politics / William G. Shade -- President John Tyler, Henry Clay and the Whig Party / Edward Crapol -- James K. Polk and the Democratic Party / M.J. Heale -- Polk in office: domestic politics and policies / Paul Bergeron -- Polk as a war president / John Pinhiero -- Polk as a southern sectionalist / Michael Todd Landis -- Zachary Taylor in office: Clay, the Whig Party, and the sectional crisis / Michael J. Birkner -- Millard Fillmore, Whig politician and leader of his party / Damon Eubank -- President Fillmore and the taming of sectionalism / Elizabeth Varon -- Franklin Pierce, democratic partisan / Yonatan Eyal -- Franklin Pierce, the Kansas-Nebraska Bill and the political transformation of the mid-1850s / John F. Kim, Jr -- James Buchanan: the early political life of the old public functionary / Jean H. Baker -- James Buchanan, the slavocracy and the disruption of the Democratic Party / James Huston -- James Buchanan and the secession crisis / John Ashworth.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 1800-1899; Presidents -- United States -- History -- 19th century; HISTORY / United States / State & Local / General; Politics and government; Presidents; Essays -- 20th century; Essays -- 21st century; Essays -- History; United States -- Politics and government -- 1837-1841.; United States -- Politics and government -- 1841-1845.; United States -- Politics and government -- 1845-1861.; United States; Electronic books; History; Electronic books